Learning from the experiences of people with HIV using general practitioner services in London: a qualitative study. Issue 4 (15th January 2016) - Keogh, Peter; Weatherburn, Peter; Reid, David
Abstract : Aim: To explore the experiences of people with HIV (PWHIV) using general practitioner (GP) services in order to identify barriers to use. Background: Traditionally, GPs have little involvement in the care of PWHIV. However, as HIV becomes a chronic condition and the population of PWHIV ages, there is a need to increase this involvement. Despite high levels of GP registration, the majority of PWHIV in London report that their GP is not involved in their HIV care. Methods: This paper presents qualitative findings from a mixed method study of PWHIV's experiences of clinical services. Survey respondents were purposively sampled to recruit 51 PWHIV who took part in eight focus groups. Participants were asked about their experience of using GP services. Findings: Three factors emerged which mediated experiences of GP care. Competence : respondents were concerned about the potential for misdiagnosis of symptoms, lack of awareness of the health needs of PWHIV and experiences of prescribing, which could lead to drug interactions. Continuity : not being able to get appointments quickly enough, not being able to see the same doctor twice and not being able to keep the same GP when one changed address were experienced as impediments to use. Communication : lack of communication between GPs and HIV specialists led to what participants called 'patient ping-pong' where they found themselves acting as a go-between for different clinical specialists trying to make sense of their care. Conclusion: Meaningful contact between HIV specialists and GPs is likely to allay concerns about competency as treatment and care decisions can be taken collaboratively between the GP, HIV specialist and patient. A key component of acceptable GP care for PWHIV is likely to be the application of long-term condition management approaches, which includes empowered patient self-management.